The complete guide to bathrooms : beautiful upgrades & hardworking improvements you can do yourself. (BLACK & DECKER Complete Guide series., 2023)
"BLACK+DECKER Complete Guide to Bathrooms brings you design advice, how-to instructions, and all the facts you need to achieve the bathroom of your dreams. This sixth edition of the perennial bestseller from the BLACK+DECKER Complete Guide series covers all the bases when it comes to bathroom remodeling. From freshening up decor to a down-to-the-studs remodel, all of the information you need to design the job and do the work yourself is right here. This new edition also features smart home projects, from advanced toilets and add-on bidets to freestanding tubs, dimmable lights, and touchless faucets. Through step-by-step photography and instructions, you'll see how to update lighting, ventilation, flooring, surfaces, cabinetry, toilets, bathtubs, and accessories. This comprehensive buyer's guide takes you through one of the most important steps in any remodeling project, and a complete and up-to-the minute section on bathroom design provides education and inspiration. It also includes information explaining how to remodel or re-imagine your bathroom to better meet the needs of aging in place, with projects that conform to Universal Design Standards. The list of projects is long and the information, vetted by the experts at BLACK+DECKER, is complete and current."--Publisher marketing.